2012
DOI: 10.1007/s10661-012-2807-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of applicability of the Sartorius Airport MD8 sampler for detection of Bacillus endospores in indoor air

Abstract: This study was designed to evaluate the measuring range and lowest limit of detection of Bacillus endospores in the ambient room air when the Sartorius MD8 sampler, and two different culture methods for bacterial enumeration were used. Different concentrations of bioaerosol were generated inside the test chamber filled with either the high-efficiency particulate air (HEPA)-filtered air or with the ambient room air. The detection of endospores in the HEPA-filtered air was achievable: (1) when they were aerosoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
2
1
Order By: Relevance
“…The number of cultivable bacteria increased with the increase in sample volume when using the MD8. This contradicts previous studies which showed no effect of sample volume on total CFU counts [ 53 ]. In addition, decreasing the flow rate from 50 L m −1 to 30 L m −1 increased the number of cultivable bacteria recovered, possibly due to the decreased impact stress placed on captured bacteria [ 54 ].…”
Section: Discussioncontrasting
confidence: 92%
“…The number of cultivable bacteria increased with the increase in sample volume when using the MD8. This contradicts previous studies which showed no effect of sample volume on total CFU counts [ 53 ]. In addition, decreasing the flow rate from 50 L m −1 to 30 L m −1 increased the number of cultivable bacteria recovered, possibly due to the decreased impact stress placed on captured bacteria [ 54 ].…”
Section: Discussioncontrasting
confidence: 92%
“…At the highest C. burnetii concentration tested, percent recovery for the AirPort MD8 was 11.6 to 43.6%, compared to 0 to 15.4% for the other two samplers tested. This finding is in line with previous studies ( 38 ); however, there was greater variability among the replicates of AirPort MD8 than in the other samplers, as also reported in previous studies of air sampling for other bacteria and fungi ( 39 41 ). The mechanism of the AirPort MD8, air filtration, has been shown to yield higher DNA amounts than liquid impingers, albeit in different contexts ( 42 , 43 ).…”
Section: Discussionsupporting
confidence: 93%
“…For each period, three batches were taken separately from different plants as shown in Table S1 . Air samples were collected by an AirPort MD8 sampler (Sartorius, Goettingen, Germany) around the soaking and cooling place of the plant 39 . The air sampler was loaded with an 80 mm, sterile, gelatin membrane filter with a pore size of 3 μm and was fixed at a height of 1.5 m above the floor.…”
Section: Methodsmentioning
confidence: 99%